Simultaneously Tuning Band Structure and Oxygen Reduction Pathway toward High‐Efficient Photocatalytic Hydrogen Peroxide Production Using Cyano‐Rich Graphitic Carbon Nitride. (16th August 2021) - Chen, Lei; Chen, Cheng; Yang, Zhi; Li, Shan; Chu, Chiheng; Chen, Baoliang
Abstract: The demands for green production of hydrogen peroxide have triggered extensive studies in the photocatalytic synthesis, but most photocatalysts suffer from rapid charge recombination and poor 2e − oxygen reduction reaction (ORR) selectivity. Here, a novel composite photocatalyst of cyano‐rich graphitic carbon nitride g‐C3 N4 is fabricated in a facile manner by sodium chloride‐assisted calcination on dicyandiamide. The obtained photocatalysts exhibit superior activity (7.01 mm  h −1 under λ ≥  420 nm, 16.05 mm  h −1 under simulated sun conditions) for H2 O2 production and 93% selectivity for 2e − ORR, much higher than that of the state‐of‐the‐art photocatalyst. The porous g‐C3 N4 with Na dopants and cyano groups simultaneously optimize two limiting steps of the photocatalytic 2e − ORR: photoactivity, and selectivity. The cyano groups can adjust the band structure of g‐C3 N4 to achieve high activity. They also serve as oxygen adsorption sites, in which local charge polarization facilitates O2 adsorption and protonation. With the aid of Na +, the O2 is reduced to produce more superoxide radicals as the intermediate products for H2 O2 synthesis. This work provides a facile approach to simultaneously tune photocatalytic activity and 2e − ORR selectivity for boosting H2 O2 production, and then paves the way for the practical application of g‐C3 N4 in environmental remediation and energy supply. Abstract : Two limiting steps in photocatalytic hydrogen peroxide synthesis are simultaneously optimized using porous g‐C3 N4 with Na dopants and cyano groups. The CN adjusts the band structure, and serves as oxygen adsorption and reduction sites, with the aid of Na +, to generate superoxide radicals as intermediates for H2 O2 production, achieving a high H2 O2 generation rate (7.01 mm  h −1 ) and selectivity (93%).